2017
DOI: 10.3329/bjas.v46i1.32172
|View full text |Cite
|
Sign up to set email alerts
|

Garbage waste induced heavy metals on roaming cattle

Abstract: Emerging evidence has shown that municipal garbage waste contains higher amount of heavy metals and increases health and environmental hazards. Little is known, however, about such wastes use as animal food to fate in products level, in dairy cattle roaming freely. To address these, garbage waste as cattle feed, feces and milk samples from roaming dairy cattle were collected from four areas and simultaneously assess heavy metals concentrations. The study areas were Aqua Morolbari (AM; used as control area), Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(2 reference statements)
0
2
0
Order By: Relevance
“…However, the contamination of cadmium in the milk samples is widely detected. For instance, Hossain, Tarafder, Hasan, Kabir, and Azad (2017) reported that the milk of roaming animals in Dhaka, Bangladesh contains 7.52 ppm cadmium on average. The animals feed on municipal garbage that has lower cadmium concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the contamination of cadmium in the milk samples is widely detected. For instance, Hossain, Tarafder, Hasan, Kabir, and Azad (2017) reported that the milk of roaming animals in Dhaka, Bangladesh contains 7.52 ppm cadmium on average. The animals feed on municipal garbage that has lower cadmium concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In the uncontrolled feed category, both animal species take their food from other sources. Alam, Kabir, Sakib, Salahuddin, and Azad (2016) and Hossain et al (2017) investigated the toxic metals in the milk of animals nourished on municipal solid waste. Hossain et al (2017) found very high chromium concentrations (10.99 ppm) in the milk of roaming animals in Dhaka, Bangladesh.…”
Section: Discussionmentioning
confidence: 99%